Research on the design and verification of the charging compatibility for electric vehicle ChaoJi charging - Xuan Zhang; Feng Ni; Min Dai; Xuling Li; Lin Sang; Lin Cheng (Energy Reports, 2022)
The international mainstream DC charging systems CHAdeMO 2.0 in Japan, GB/T 2015 in China, CCS1/CCS2 in Europe, and the U.S. have different control pilot circuit and the coupler designs. Control pilot circuit is an important component of the electric vehicle (EV) charging system and is used to monitor the function of the interaction between the EV and the electric vehicle supply equipment (EVSE). Existing system designs can make the difficult to achieve the compatibility between different charging systems, and reduce the user experience. This study first analyzes the practical applications of four existing mainstream DC charging systems. There are certain defects in structural design, safety, compatibility, and control pilot function, the introduction of a new generation of ChaoJi charging technology will change all these. Meanwhile the vehicle adapter design solution can perfectly solve the problem of physical compatibility between the existing charging system and ChaoJi vehicle. In addition, a new control pilot circuit design is proposed, to identify normal charging and abnormal states by hard node signals and states switches. By building a test environment, this new control pilot circuit has proven to its excellent characteristics in terms of fault monitoring, backward compatibility, and future-proof applications. ChaoJi charging technology has been adopted by CHAdeMO 3.0, laying the foundation for a globally harmonized charging system.